Macrotransport properties of aerosol particles in the human oral-pharyngeal region - Tey, Cheng Hwee. (2008)
Local distributions of an inhaled aerosol bolus in the large central human airways are studied numerically by applying the FLUENT CFD (computational fluid dynamics) software package. Focusing on a rigid, symmetric double in-plane bifurcation lung airway model, a finite volume program has been employed to simulate the airflow.